Proceedings of the 2018 ACM/IEEE International Conference on Human-Robot Interaction 2018
DOI: 10.1145/3171221.3171264
|View full text |Cite
|
Sign up to set email alerts
|

Planning with Trust for Human-Robot Collaboration

Abstract: Perspective-taking is the ability to perceive or understand a situation or concept from another individual's point of view, and is crucial in daily human interactions. Enabling robots to perform perspective-taking remains an unsolved problem; existing approaches that use deterministic or handcrafted methods are unable to accurately account for uncertainty in partially-observable settings. This work proposes to address this limitation via a deep world model that enables a robot to perform both perception and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
127
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(140 citation statements)
references
References 30 publications
0
127
0
Order By: Relevance
“…Misplaced trust in robots can lead to poor task-allocation and unsatisfactory outcomes. In recognition of its importance, there has been a concerted effort in the research community to better understand the formation and dynamics of trust in robots and automation [4]- [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Misplaced trust in robots can lead to poor task-allocation and unsatisfactory outcomes. In recognition of its importance, there has been a concerted effort in the research community to better understand the formation and dynamics of trust in robots and automation [4]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there remains crucial gaps in our understanding of human-robot trust, particularly in the role of inferred robot "intention", i.e., what people believe the robot is trying to achieve. Prior research has focussed largely on inferred capability [7], [9], [10], which has been shown to be a primary antecedent to trust [11], [12]. However, with the advancement of robot technology (e.g., artificial intelligence), robots are increasingly poised to achieve peer-like collaboration with humans.…”
Section: Introductionmentioning
confidence: 99%
“…Most relevant here is work by Chen et al [6], who treat the human's trust as a latent variable, and integrate trust into the robot's decision making. These previous works [3]- [6] consider cases where the human and collaborative robot share a common objective and the robot should maximize trust; by contrast, we are interested in robots that leverage trust to influence users.…”
Section: Related Workmentioning
confidence: 99%
“…Here, we revisit the two-player game outlined in Section III-A, and use the trusting human model (6) to reformulate this game as an instance of a single-agent Markov decision process (MDP). Expressing the trusting human model as an MDP enables us to leverage existing methods to solve for u * ,τ r .…”
Section: A Trusting Humans As a Markov Decision Processmentioning
confidence: 99%
See 1 more Smart Citation